Peran Penting Lembaga Kearsipan dalam Melestarikan Budaya dan Sejarah Daerah melalui Digitalisasi Arsip Statis: Studi Kasus Kantor Arsip Daerah Kota Cimahi - Waluya, Muhamad Rizaldy; Setiawati, Linda; Khoerunnisa, Lutfi (Universitas Negeri Padang, 2023)
The purpose of this research is to provide an overview of the importance of digitizing archives in this digital era to maintain the efficiency and accessibility of archives. The research method used is research with a qualitative approach to literature studies, interviews and observations. Primary data was obtained by observing the Cimahi City Static Archives website and literature study, while secondary data was obtained from interviews conducted with Expert Archivists at the Cimahi City Archives Service. The results of this study indicate that digitizing archives is an important step in maintaining archives that have historical value, so that the information contained in these archives can be preserved for the future. This digitization of archives can overcome problems in archive management such as a lack of efficiency in archive management and lack of accessibility to obtain information from existing archives. The Cimahi City Archives Service has made efforts to digitize archives related to the main performance index of the Cimahi City Archives Service itself, namely to increase community literacy and adapt to technological developments. Improving community literacy is carried out by presenting publications that can be a source of information for the public regarding history in Cimahi City, thus history in Cimahi City continues to be passed on to future generations because it has been stored in a digital media.